Electrical and thermal stimulus-responsive nanocarbon-based 3D hydrogel sponge for switchable drug delivery. Issue 6 (28th January 2022) - Park, Sang-Yu; Kang, Ji-Hye; Kim, Han-Sem; Hwang, Ji-Young; Shin, Ueon Sang
Abstract : The CNT sponge-based 3D frame hydrogel showed remarkable responses to electrical and thermal stimuli, exhibited excellent controllable/switchable drug delivery, and has great potential in biomedical engineering and medicine applications. Abstract : Smart hydrogels that are responsive to various external ( e.g. electrical and/or thermal) stimulation have become increasingly popular in recent years for simple, rapid, and precise drug delivery that can be controlled and turned on or off with external stimuli. For such a switchable drug delivery material, highly homogeneous dispersion and distribution of the hydrophobic, electrically conductive nanomaterials throughout a hydrophilic three-dimensional (3D) hydrogel network remains a challenge and is essential for achieving well-connected electrical and thermal conducting paths. Herein we developed electrical and thermal stimulus-responsive 3D hydrogels based on (i) carbon nanotubes (CNTs) as the core unit and an electrical/thermal conductor, (ii) chitosan (Chit) as the shell unit and a hydrophilic dispersant, and (iii) poly(NIPAAm- co -BBVIm) (pNIBBIm) as the drug carrier and a temperature-responsive copolymer. By formulating the CNT-core and Chit-shell units and constructing a CNT sponge framework, uniform distribution and 3D connectivity of the CNTs were improved. The 3D hydrogel based on the CNT sponge, namely the 3D frame CNT–Chit/pNIBBIm hydrogel, delivered approximately 37% of a drug, ketoprofen used for the treatment of musculoskeletal pain, during about 30% shrinkage after electrical and thermal switches on/off and exhibited the best potential for future use in a smart transdermal drug delivery system. The physicochemical, mechanical, electrical, thermal, and biocompatible characteristics of this nanocarbon-based 3D frame hydrogel led to remarkable electrical and thermal stimulus-responsive properties capable of developing an excellent controllable and switchable drug delivery platform for biomedical engineering and medicine applications.